THE ROLE OF 4OCEAN IN CLEANING UP OF MARINE DEBRIS IN BALI IN 2022-2023 - Ramadhony, Farid; Suryani, Irma (Universitas prof. Dr. Moestopo (Beragama), 2024)
The garbage piled up in the ocean can be caused by household waste and increasing marine tourism and shipping activities. The increase of marine debris is an international case because it has impacted the global climate crisis resulting in the damage of marine ecosystems. Those large impacts caused by pollution in the ocean prompted many parties to make regulations regarding the marine debris crisis. In carrying out its project, 4ocean cleans up the garbage by transporting it from rivers, coasts, and the ocean, then brings it to the land and processes it into recycled products. The 4Ocean teams work using environmentally friendly equipment. 4Ocean cleans the ocean by removing around one million pounds of garbage every month. This project can help the government tackle the marine waste crisis. The method used in this research is a literature study where the author collects data through previous writings and searches for data from the internet. This research aims to look at the role of international organizations as one of the actors in international relations in dealing with the waste crisis.